Surgical Resection of Ruptured Fibrolamellar Hepatocellular Carcinoma. (18th July 2013) - Minutolo, Vincenzo; Licciardello, Alessio; Arena, Manuel; Minutolo, Orazio; Lanteri, Raffaele; Arena, Goffredo
Abstract : Fibrolamellar hepatocellular carcinoma (FLH) is a rare primary tumor of the liver, which typically arises from noncirrhotic livers and affects patients below the age of 35. We report on a 29-year-old male patient who presented with a ruptured FLH and was treated with surgical resection. Options for treatment and review of the management are described.